2022
DOI: 10.1186/s13561-022-00386-8
|View full text |Cite
|
Sign up to set email alerts
|

Pooled coverage of community based health insurance scheme enrolment in Ethiopia, systematic review and meta-analysis, 2016–2020

Abstract: Background Community Based Health Insurance (CBHI) is a type of health insurance program that provides financial protection against the cost of illness and improving access to health care services for communities engaged in the informal sector. In Ethiopia, the coverage of CBHI enrolment varies across regions and decision of household enrolment is affected by different factors. There are pocket studies on CBHI scheme with different coverage in Ethiopia and there is no pooled study on CBHI enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Based on the concepts of UHC, the qualitative findings of the included studies were thematized into five categories. PC : The PC of the CBHI has gradually been expanded [ 38 , 41 , 42 ]. HSU : CBHI improved HSU [ 36 , 43–56 ], such as antenatal care (ANC) visits [ 43 ]; child healthcare visits [ 44 , 47 ]; seeking treatment for malaria [ 46 ]; in-patient [ 36 ] and outpatient [ 49 , 50 ] attendances; frequency of visits [ 49 , 53 ]; and family planning [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the concepts of UHC, the qualitative findings of the included studies were thematized into five categories. PC : The PC of the CBHI has gradually been expanded [ 38 , 41 , 42 ]. HSU : CBHI improved HSU [ 36 , 43–56 ], such as antenatal care (ANC) visits [ 43 ]; child healthcare visits [ 44 , 47 ]; seeking treatment for malaria [ 46 ]; in-patient [ 36 ] and outpatient [ 49 , 50 ] attendances; frequency of visits [ 49 , 53 ]; and family planning [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pooled UHC by CBHI was found to be 45.6%. Regarding PC, according to the three national studies included in this review, 40.10% of the households were found to be covered by the scheme, with the lowest, medium, and highest coverages being 28% [ 38 ], 45% [ 42 ], and 45.5% [ 41 ], respectively. Coming to the impact of CBHI on HSU, the pooled report of the 13 included studies showed that the HSU among CBHI members was 64.5%.…”
Section: Resultsmentioning
confidence: 99%
“…The CBHI benefit package covers all outpatient and inpatient services at the contracted public health centers and hospitals (through referral system) except dental, optic and cosmetic procedures [24]. Most recent enrollment estimations indicate that about 45-50% of the population is enrolled [25,26]. In 2018, overall CBHI enrolment in the study woreda was 64%.…”
Section: Introductionmentioning
confidence: 99%